Retroperitoneoscopic pyeloplasty with simultaneous pyelolithotomy using a flexible cystoscope: Our initial experience at a single centre - Zhang, Fei; Wang, Li; Gao, ZheBin; Yang, HouMeng (Frontiers in Surgery, 2022)
ABSTRACT Purpose: We present our experience with retroperitoneoscopic pyeloplasty with simultaneous pyelolithotomy using a flexible cystoscope in patients with ureteropelvic junction obstruction(UPJO) complicated with kidney stones. Materials and Methods: The records of 37 patients who underwent retroperitoneoscopic pyeloplasty with simultaneous pyelolithotomy using a flexible cystoscope to manage UPJO complicated with kidney stones from July 2015 to December 2020 were retrospectively reviewed. All patients underwent one-stage retroperitoneoscopic pyeloplasty combined with flexible cystoscopic pyelolithotomy. The operative time, blood volume, stone clearance rate, length of hospital stay, complications and follow-up events were recorded. Results: The operation went smoothly in all 37 patients. The mean operative time was 148.4±24.2 min. The mean intraoperative blood loss volume was 54.3±20.5 ml. The mean hospitalization time was 10.6±3.7 days. The stone clearance rate was 81.08%. The mean follow-up period was 23.5 months (range 12-53 months). Hydronephrosis was significantly decreased in 33 of the 37 cases. The success rate of the operation was 89.19%. Stones recurred in 9 patients during follow-up, for a recurrence rate of 24.32%. Conclusion: Retroperitoneoscopic pyeloplasty with simultaneous pyelolithotomy using a flexible cystoscope in patients with UPJO complicated with kidney stones is safe, effective and worthy of promotion.